2003
DOI: 10.1038/422493a
|View full text |Cite
|
Sign up to set email alerts
|

Are fast-moving elephants really running?

Abstract: Objective: To describe the clinical characteristics and outcomes in a population of dogs with negative-pressure pulmonary edema (NPPE) and to identify the main causes of the disease. To evaluate any associations with morbidity and mortality.Design: Retrospective study.Setting: Three university teaching hospitals and two private referral centers.Animals: Thirty-five client-owned dogs presented with NPPE. Interventions: NoneMeasurements and Main Results: Data collected included patient characteristics, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
135
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 9 publications
5
135
1
Order By: Relevance
“…Elephants do not normally trot or gallop, even as juveniles, but they can move smoothly to fairly fast speeds (approx. 6.8 m s K1 ) without changing their lateral sequence footfall pattern (Hutchinson et al 2003). Their locomotor pattern at their faster speeds is atypical of most familiar quadrupedal animals (Muybridge 1899;Gambaryan 1974;Hildebrand 1985).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Elephants do not normally trot or gallop, even as juveniles, but they can move smoothly to fairly fast speeds (approx. 6.8 m s K1 ) without changing their lateral sequence footfall pattern (Hutchinson et al 2003). Their locomotor pattern at their faster speeds is atypical of most familiar quadrupedal animals (Muybridge 1899;Gambaryan 1974;Hildebrand 1985).…”
Section: Introductionmentioning
confidence: 96%
“…However, when applied to the fast moving elephants, they are partly contradictory (Hutchinson et al 2006). Previous studies doubted whether fast moving elephants were merely walking (Hutchinson et al 2003), but the speed at which any potential gait transition occurred was left open, although it was concluded that near a dimensionless speed of 1.0 (equal to Fr 0.5 , 1.0) elephants probably were running, in the mechanical sense of the term.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations